Carbofuran cytotoxicity, DNA damage, oxidative stress, and cell death in human umbilical vein endothelial cells: Evidence of vascular toxicity. Issue 5 (25th February 2021) - Saquib, Quaiser; Siddiqui, Maqsood A.; Ansari, Sabiha M.; Alwathnani, Hend A.; Al‐Khedhairy, Abdulaziz A.
Abstract: Carbofuran is a broad‐spectrum carbamate insecticide, which principally inhibits the acetylcholinesterase (AChE) enzyme in the nervous system. Nonetheless, their selective action is not restricted to a single species and expanded to humans. No studies are available on the toxicological effects of carbofuran in the endothelial cells (ECs), which first confronts the toxicants in blood vessels. Hence, we have exposed the human umbilical vein ECs (HUVECs) with carbofuran for 24 h, which significantly reduced the cell survival to 25.16% and 33.48% at 500 and 1, 000 μM analyzed by MTT assay. In the neutral red uptake (NRU) assay, 16.68%, 30.99%, and 58.11% survival decline was found at 250, 500, and 1, 000 μM of carbofuran. HUVECs exposed to carbofuran showed significant increase in the intracellular reactive oxygen species (ROS), indicating oxidative stress at low concentrations. In parallel, HUVECs showed hyperpolarization effects in the mitochondrial membrane potential (ΔΨm) upon carbofuran exposure. Carbofuran induced DNA damage in HUVECs measured as 8.80, 11.82, 35.56, and 79.69 Olive tail moment (OTM) in 100‐, 250‐, 500‐, and 1, 000‐μM exposure groups. Flow cytometric analysis showed apoptotic peak (SubG1) and G2M arrest in the HUVECs exposed to carbofuran. Overall, our novel data confirm that carbofuran is toxic for the EC cells, especially at the higher concentrations, which may affect the vascular functions and possibly angiogenesis. Hence, carbofuran should be applied judiciously, and detailed vascular studies are warranted to gain an in‐depth information focusing the transcriptomic and translation changes employing suitable in vivo and in vitro test models. Abstract : Herein carbofuran toxicity was analyzed in HUVECs, as a model of endothelial cells. Carbofuran showed significant cytotoxicity, oxidative stress, and mitochondrial dysfunction from low to high exposure concentrations. HUVECs exposed to carbofuran exhibited DNA damage, G2M arrest and apoptosis in HUVECs analyzed by comet assay and flow cytometry. This is a first report on HUVECs validating carbofuran toxicity, which may induce a comparable effect in the human vascular cells and may affect angiogenesis.